Upaya Meningkatkan Kemampuan Perilaku Prososial Anak Usia 5 – 6 Tahun melalui Permainan Boneka Jari Tangan di RA Al Adzkiya 02 Kota Cianjur - Vina Fauziah Asyri; Usep Dimyati; Uswatun Hasanah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Prosocial behavior is an important social skill for early childhood to build positive interactions with their surroundings. This study aims to improve the prosocial behavior skills of children aged 5–6 years through finger puppet games at RA Al Adzkiya 02, Cianjur City. The method used is classroom action research (CAR) with two cycles, which include the planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that finger puppet games can improve various aspects of prosocial behavior, such as sharing, helping, working together, and understanding other people's feelings. In each cycle, there was an increase in children's prosocial behavior observation scores, which shows the effectiveness of this method. Children become more active in interacting, more empathetic towards peers, and more easily understand the concept of cooperation and helping each other. Thus, finger puppet games can be used as an interesting and effective learning strategy in developing early childhood social skills. Teachers and educators are advised to integrate this method into learning activities in order to stimulate children's social-emotional development optimally.